Supplementation of ammoniated wheat straw in wintering diets of gestating beef cows - Beck, T.J.; Simms, D.D.; Brandt, Robert T., Jr.; Cochran, R.C.; Kuhl, Gerry L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
During two winters, 96 beef cows in late gestation were utilized in 60-day precalving feeding trials to evaluate supplementation for cows fed ammoniated wheat straw. Treatments included: control--mineral supplement only (C), 3 lbs milo + mineral (3M), 6 lb milo + mineral (6M), and 2.75 lb milo + .75 lb soybean meal + mineral (SBM). 3M increased (P<.05) cow gain over control but body condition changes were similar. 6M and SBM resulted in similar gains and body weight changes, which were higher than those of cows receiving either C or 3M. Birth weight of calves, percent cycling at the start of breeding, and percent pregnant after a 60-day breeding season were not affected by treatment. Natural protein appears to be a major limiting nutrient in cows fed ammoniated wheat straw.
Keywords: Beef; Ammoniation; Wheat straw; Cows; Supplementation